Enhanced near‐infrared to green upconversion from Er3+‐doped oxyfluoride glass and glass ceramics containing BaGdF5 nanocrystals. (30th September 2016) - Biswas, Kaushik; Balaji, Sathravada; Ghosh, Debarati; Kalyandurg, Annapurna
Abstract: In this work, effect of glass composition as well as ceramization on visible and near‐infrared (NIR) luminescence properties along with their decay dynamics of Er 3+ ions has been compared considering two different oxyfluoride glasses yielding BaF2 and BaGdF5 nanocrystals. Both the glass systems have exhibited an intense normal and upconversion green emission under ultraviolet (378 nm) and NIR (978 nm) excitations, respectively. A remarkable enhancement of these emission intensities is observed for gadolinium‐(Gd) containing glasses. Interestingly, NIR fluorescence intensity from Er 3+ ions at 1540 nm has showed marginal decrease in gadolinium‐containing glass which is attributed to occurrence of strong excited‐state absorption (ESA) due to higher fluorine content ensuing an augmentation of upconversion green emission with a concomitant decrease in NIR emission. The quadratic dependence of upconversion green emission intensity on its pump power for all the samples revealed biphotonic absorption process from ground‐state 4 I15/2 to the excited‐state 4 I11/2 followed by ESA of second photon to the 4 F7/2 level. The intense green upconversion emission as well as enhanced NIR fluorescence lifetimes indicate the suitability of these glass/glass ceramics for upconversion lasers and amplification in the third telecom window.